Analisis Pelaksanaan Tugas Unit Apron Movement Control pada Event MotoGP Mandalika di Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - M.Qifhar Anugrah Ramadhan; Desiana Rachmawati (Jurnal Transformasi Bisnis Digital, 2025)
The rapid development of Lombok tourism and the MotoGP event will be held in September 2024, driving the need for transportation, especially air transportation, Zainuddin Abdul Madjid Lombok International Airport has several units that play a role in optimizing the airport, one of which is the Apron Movement Control (AMC) unit, this unit has a very important role in supervising all traffic movements on the air side which includes aircraft parking stands, traffic of people, vehicles, and Ground Handling arrangements, flight data administration and licensing of vehicles operating on the apron, this study aims to determine the differences in the implementation of the AMC unit's duties before and during the Mandalika MotoGP event, and to determine the obstacles faced when carrying out tasks during the event. This study uses a qualitative method, the data used are primary and secondary data, primary data is obtained from observation and interviews, while secondary data from SOP, documentation in the form of photos and regulations related to the problem being studied, data analysis techniques use data reduction, data presentation and drawing conclusions, testing the validity of data using triangulation techniques. This study shows that AMC officers successfully carried out their duties in accordance with SOP, including the process of plotting aircraft parking, operating Aviobridge, supervising Ground Support Equipment and supervising Marshaller Service, the responsibility of officers in providing services to airport users, especially in the Airside area, was carried out well, the obstacles faced including FOD, lack of facilities and personnel available, use of Driving Licenses and the suitability of vehicles/equipment and lack of communication between units can be handled and provide evaluation so that all movements in the Airside area run smoothly.